Relationship between Emotional Intelligence and School Anxiety in Basic Secondary School Students in Montería, Colombia - Murillo , Hernán Javier Guzmán; Ortega, José Marcelo Torres; Niebles, William (Journal of Ecohumanism, 2024)
The present study aims to analyze the relationship between emotional intelligence and school anxiety in adolescent secondary school students in the city of Montería, Colombia. The sample consisted of 160 students randomly selected from a total population of 280, belonging to 10th and 11th grades, aged between 15 and 18 years. A quantitative, descriptive-correlational research design was applied, using the Trait Meta-Mood Scale (TMMS-24) and the State-Trait Anxiety Inventory (IDARE) for data collection. Results did not show a statistically significant correlation between emotional intelligence and school anxiety in the general scores. However, a weak positive correlation was identified between the anxiety trait dimension and emotional intelligence, suggesting that moderate anxiety levels may be associated with higher emotional perception among adolescents. These findings highlight the importance of strengthening emotional competencies within the school context to promote mental health and improve academic performance.